Analaysis Of Agro Processing Industry In Punjab, India - Dr.Veerinder Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Punjab is a state dominated by agriculture, an agro-processing industry can be established to boost the agricultural business system, which will enhance the completion of that procedure in any other component of the agri-business system. Economic liberalisation, globalisation, and MNCs' inclusion in the processed agro-industry have increased market and competitiveness prospects significantly, giving customers an advantage. The probable modernization and commercialization of agriculture after GATT concentrated on domestic and foreign agro value-adding products marked a promising future for the Punjab agri-food industry. The domestics of this survey took account of the evolving tastes and preferences of consumers for processed agro-products. This research focused on the domestic market. This paper analyzed the creation and financial performance of selected agro-processing industries, including food grain breaking, processing of edible oilseeds, processing sugar cane, and dairy products producing mass consumption products. It focuses on these businesses for advancement centered on performing parameters and addresses policies